The Use of Innovative Techniques in the Educational Process of Pedagogical College - Chemerys, Iryna (Pedagogical Discourse, 2015)
The problem of the use of innovative techniques in the educational process in preparation of the future teachers to innovative professional activity has been studied in the article; the tendencies of innovative activity development of pedagogical college have been analyzed; the definitions «innovation», «innovative activity» have been determined; the main tasks of innovative work have been cleared out; the experience of educational work with the use of innovations in pedagogical college has been described; introduction of innovative technologies into the educational process as one of the most important questions, which are studied worldwide nowadays, has been examined; the position of a teacher in the process of use of innovation, as a subjective factor is crucial during the introduction and spread of innovation, has been traced.